10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Community health workers (CHWs) play increasingly important roles in vector-borne disease prevention globally, yet their contributions remain underutilized and poorly documented in the literature. Understanding how CHWs are deployed across the prevention continuum and identifying barriers to their effectiveness is essential for strengthening mosquito-borne disease control programs. OBJECTIVES: (1) describe the scope and characteristics of studies engaging Community Health Workers (CHWs) in vector-borne disease prevention through community-based strategies; (2) organize the findings by public health prevention levels-primary, secondary, and tertiary-to highlight their impact on CHW knowledge, attitudes, and practices; and (3) identify cross-cutting themes related to facilitators and barriers affecting CHW integration and effectiveness in vector-borne disease control programs. METHODS: This scoping review followed PRISMA-ScR guidelines (Page et al. 2021). Five databases (PubMed, ProQuest, Scopus, Science Direct, and LILACS) were systematically searched for peer-reviewed studies published between 2000 and 2024. Studies were included if they examined CHW-led community-based educational interventions targeting mosquito-borne diseases. Two reviewers independently screened articles using Rayyan.ai software, with an iterative two-stage process: 1. Title, keyword, and abstract review, and 2. Full-text assessment. Data were extracted and organized using public health prevention framework. RESULTS: Fourteen studies met inclusion criteria. CHWs served critical functions across the disease prevention and control continuum, including health education delivery, early case detection, community mobilization, treatment adherence support, and vector control activities. The evidence synthesis revealed persistent systemic barriers that compromise CHW effectiveness, including insufficient training protocols, resource constraints, and role ambiguity within existing healthcare frameworks. Through an application of a public health prevention frameworks encompassing primary, secondary, and tertiary interventions, this scoping review identified both evidence-based best practices and significant implementation gaps. CONCLUSION: The findings demonstrate that while CHWs represent a vital human resource for mosquito-borne disease control, their potential impact remains underutilized due to inadequate institutional support structures. The scarcity of rigorous research reveals a critical gap in the evidence base that must be addressed through systematic evaluation of CHW programs, particularly regarding effectiveness, sustainability, and optimal integration models.